CLEANER PRODUCTION IN OPEN INNOVATION PERSPECTIVE AT SMALL AND MEDIUM INDUSTRIES (SMIS) BATIK - Asih Rumanti, Augustina
Cleaner production is a reduction in the amount of waste by implementing strategies that are carried out continuously to prevent environmental damage and increase efficiency and reduce negative impacts on humans and the environment. The implementation of cleaner production has been carried out in the manufacturing industry by several developed countries, however its implementation in small and medium industries is still low. The limitation of cleaner production in small and medium industries is due to a lack of awareness of the importance of produce products that are safe for the environment. Implementation of cleaner production in small and medium industries have limitation that can be overcome by innovation, however innovation carried out internally (closed innovation) have not provided optimal support in achieving cleaner production. It takes the involvement of external parties (stakeholders) in helping small and medium industries (SMIs) to achieve cleaner production. Innovation that involves external parties in innovation activities on organization is called open innovation. This study involves 182 SMIs batik as respondents. The respondents are located in Laweyan (Surakarta), Madura, and Lasem (Rembang). The research model is constructed to achieve cleaner production through the implementation of open innovation at batik SMIs which is supported by the open innovation climate. There is environmental dynamism and environmental competitiveness as a moderator for the relationship between open innovation climate and open innovation. The results of testing the measurement model and structural model state that the accepted hypothesis is that open innovation has a positive effect on cleaner production (H1); open innovation climate has a positive influence on open innovation (H2); and environmental dynamism as a moderator that can strengthen the influence of open innovation climate on open innovation (H3) statistically significant, while environmental competitiveness moderator is not statistically proven to strengthen the effect of open innovation climate on open innovation (H4). Based on the hypothesis testing, a mapping of the position of open innovation on cleaner production was carried out. The position of the SMIs Batik in each quadrant was analyzed / explored by depth interviews.. The results of the mapping divided the SMIs into four quadrants. Quadrant I is for SMIs that do not yet have the ability to carry out the open innovation process at the same time as being unable to achieve cleaner production. Quadrant II is for SMIs that have the ability to achieve cleaner production, but this has not been based on the open innovation process. Quadrant III is for SMIs that already have the ability to do the open innovation process but have not yet supported to achieve cleaner production. Quadrant IV is for SMIs that have the ability to achieve cleaner production and are supported by the open innovation process.